Rescue stenting after the failure of mechanical thrombectomy to treat acute intracranial atherosclerotic occlusion - Guo, Shunyuan; Jin, Tianyu; Xu, Chao; Huang, Wei; Shi, Zongjie; Geng, Yu (Frontiers in Neurology, 2023)
Background: Acute ischemic stroke (AIS) with intracranial large vessel occlusion(LVO) are refractory to reperfusion because of underlying intracranial atherosclerosis (ICAS), often requiring salvage method such as balloon angioplasty, rescue stenting(RS), and so on. In this study, we investigate the safety and efficacy and short-term outcomes of RS after failed mechanical thrombectomy (MT) for acute intracranial atherosclerotic occlusion. Methods: We retrospectively evaluated the clinical data of 127 patients who underwent MT for acute intracranial atherosclerotic occlusion in our hospital between August 2018 and January 2022. The recanalization degree immediately after the treatment was evaluated by Modified Thrombolysis in Cerebral Infarction (mTICI). Modified Rankin Scale (mRS) was applied 90 d after treatment to evaluate the neurological functions. In addition, incidences of symptomatic intracranial hemorrhage (sICH) and postoperative mortality within 90 d of treatment were calculated. Results: Among the 127 patients, 86 patients (67.7%) had revascularization (mTICI 2b-3) immediately after MT (non-RS group), RS was performed in 41 patients (32.3%) after failure of MT (RS group). No difference in the rate of sICH was found between the two groups (17.1 % versus 16.3%, P=0.91). There was a slightly higher rate of mortality in the RS group (14.6% versus 12.8%, P=0.71), however, the difference was not significant. There was no difference in 90 d mRS of 0 to 2 (48.8 % versus 52.3%, P=0.76) between patients in the RS and non-RS groups. Conclusions: RS after failure of MT is a safe and effective method for acute intracranial atherosclerotic occlusion.